AN ANALYSIS ON THE FACTORS WHICH INFLUENCE AUDITORS’ PERFORMANCE AT THE INSPECTORATE OFFICE OF NORTH SUMATERA PROVINCE WITH THEIR MOTIVATIONAS MODERATING VARIABLE - Friska, Mei Sinaga (Asosiasi Dosen Akuntansi Indonesia, 2018)
The objective of the research was to examine the factors which influenced auditors’ performance at the Inspectorate Office of North Sumatera Province with their motivation as moderating variable. The research used explanatory research method by using primary data. The population was all functional officials at the Inspectorate Office of North Sumatera Province, and 31 of them were used as the samples. The hypothesis was tested by using multiple linear regression analysis, and moderating variable was tested by using the change in coefficient determination test. The result of the research showed that, simultaneously, the level of education, sustainable education, independence, experience, and knowledge had positive and significant on auditors’ performance. Auditors’ motivation as moderating variable was able to moderate the correlation of the level of education, sustainable education, independence, experience, and knowledge with auditors’ performance.